2007
DOI: 10.1002/pola.22263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the terminal substituent of azobenzene on the properties of ABA triblock copolymers via atom transfer radical polymerization

Abstract: The effect of the terminal substituent of azobenzene on the properties of ABA triblock copolymers was investigated. For this study, three kinds of azobenzene-containing monomers with different terminal substituents-6-[4-(4-methoxyphenylazo)phenoxy] hexyl methacrylate, 6-[4-(4-ethoxyphenylazo)phenoxy]hexyl methacrylate, and 6-[4-(4nitrophenylazo)phenoxy]hexyl methacrylate-were used to synthesize ABA triblock copolymers PMMAzo 25 -PEG 13 -PMMAzo 25 /PMMAzo 12 -PEG 13 -PMMAzo 12 , PEMAzo 14 -PEG 13 -PEMAzo 14 , a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Figure shows functional monomers (FM- 79 to FM- 99 ), all acrylates and methacrylates, thus far employed for liquid crystalline and optically active polymers via metal-mediated living radical polymerization with copper salts (CuBr or CuCl) and multidentate aliphatic amine ligands (PMDETA or HMTETA). Though monomer conversion is invariably at most about 50%, polymer molecular weights were generally controlled with M w / M n < 1.3, independent of the pendants structures.…”
Section: Precision Polymer Synthesismentioning
confidence: 99%
“…Figure shows functional monomers (FM- 79 to FM- 99 ), all acrylates and methacrylates, thus far employed for liquid crystalline and optically active polymers via metal-mediated living radical polymerization with copper salts (CuBr or CuCl) and multidentate aliphatic amine ligands (PMDETA or HMTETA). Though monomer conversion is invariably at most about 50%, polymer molecular weights were generally controlled with M w / M n < 1.3, independent of the pendants structures.…”
Section: Precision Polymer Synthesismentioning
confidence: 99%
“…A variety of azo-containing sidechain LCPs with different molecular structures have been prepared via various polymerization approaches. 1,3,4,6,7,[12][13][14][15][16][17][18][19][20][21][22] Systematic studies on the structure-property relationship of the azo-containing side-chain LCPs have revealed that both their phase transition behaviors and photoresponsive properties are strongly dependent on their polymer backbones, 13,14 the azo mesogens, [15][16][17][18] and the length of the flexible spacers. [19][20][21][22] Among these influencing factors, the molecular structures of the azo mesogens, especially the terminal substitutent of the azo groups, have been recognized as one of the most important primary factors influencing the properties of the azo polymers because the azo groups act as both the mesogenic and photoresponsive units and their substituents can have significant influence on the dipole moment of the azo chromophores and thus their phase transition and photoresponsive behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Among these influencing factors, the molecular structures of the azo mesogens, especially the terminal substitutent of the azo groups, have been recognized as one of the most important primary factors influencing the properties of the azo polymers because the azo groups act as both the mesogenic and photoresponsive units and their substituents can have significant influence on the dipole moment of the azo chromophores and thus their phase transition and photoresponsive behaviors. [15][16][17][18] Therefore, many side-chain LCPs bearing pendant azo mesogens with various substituents such as hydrogen, 23 alkyl, 24,25 perfluoroalkyl, 17 alkyloxy, 15,26,27 chiral alkyloxy, 21,28 nitro, 19,29,30 cyano, 31,32 carboxyl, 33 cinnamoyl, 34,35 and N-hydroxysuccinimide carboxylate groups 36 have been developed for different purposes.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Among them, the combshaped side-chain LCPs with pendant azo groups have been the most extensively investigated materials up to now. 2,[4][5][6][7] To be suited for different application purposes, many sidechain LCPs bearing pendant azo mesogens with different substituents such as hydrogen, 11,12 alkyl, 13,14 perfluoroalkyl, 15 alkyloxy, [16][17][18] chiral alkyloxy, 19,20 nitro, [21][22][23] cyano, 24,25 carboxyl 26 and cinnamoyl group 27,28 have been developed. Among them, the side-chain LCPs bearing azo mesogens with reactive substituting groups are particularly interesting because of their combined properties of liquid crystallinity, photoresponsivity and reactivity.…”
Section: Introductionmentioning
confidence: 99%